Critical Pedagogy and Teacher Education in the Neoliberal Era Small Openings - Groenke, Susan L.; Hatch, J. Amos (Explorations of Educational Purpose, 2009)
The chapters in this edited collection make it clear that critical teacher educators are aware of neoliberalism and its profound impact on public schools and university-based teacher preparation programs. They know the deleterious effects of macro-level, neoliberal forces on the local and particular teaching contexts where they are trying to do critical pedagogical work. The authors describe the havoc NCLB has wreaked, especially on minority and ELL students; the pressures university-based teacher preparation programs feel to align themselves with neoliberal agendas; and the frustration of knowing that critical work is not always valued, supported, or understood in academe. Yet all of the authors in this book persist, finding or creating "small openings" in their contexts that foster the critical reflection, intellectual engagement, and examination of alternative paradigms that help beginning teachers pursue deeper understandings about schooling in a democratic society. They describe these openings here.